Introducing global food 50/50: Brief prepared for the UN Food Systems Pre-Summit 2021 - Global Health 50/50; International Food Policy Research Institute; Tanaka, Sonja; Njuki, Jemimah (Global Health 50/50, 2021)
Gender equality is a precondition for achieving the world’s shared ambitions of the Sustainable Development Goals by 2030, including delivering sustainable food systems. Gender is intricately linked to all components of food systems. Gender inequalities are both a cause and an outcome of unsustainable food systems and unjust food access, consumption, and production. In the lead-up to the 2021 UN Food Systems Summit, IFPRI and its partners have selected 10 transformative areas of action to promote gender-equitable food systems. One of these areas is gender-responsive and gender-equitable leadership in food systems under Action Track 1 on Ensuring Access to Safe and Nutritious Foods. Among these actions, stakeholders have committed to establishing a global mechanism to monitor progress and hold food systems organizations accountable for achieving gender equality in leadership, setting gender-equitable internal workplace policies, and implementing strategies that advance progress toward gender-just and equitable food systems.